Increasing Mortality From Premature Coronary Artery Disease in Women in the Rural United States - Bossard, Matthias; Latifi, Yllka; Fabbri, Matteo; Kurmann, Reto; Brinkert, Miriam; Wolfrum, Mathias; Berte, Benjamin; Cuculi, Florim; Toggweiler, Stefan; Kobza, Richard; Chamberlain, Alanna M.; Moccetti, Federico (Journal of the American Heart Association, 2020)
Background Previous reports have described a leveling off of mortality from premature coronary artery disease (CAD). In recent years, the prevalence of cardiovascular risk factors has increased in rural communities and young adults. Methods and Results We extracted CAD mortality rates from the Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER) database from 1999 to 2017, focusing on mortality from premature CAD (defined as <65 years of age in women) and urban-rural differences. Variations in mortality rates over time, assessed with Joinpoint regression modeling, are expressed as estimated annual percentage change (95% CI) and stratified by urbanization, sex, age, and race. Age-adjusted mortality rates decreased for women and men. Stratification by urbanization revealed that premature CAD mortality is stagnating among women in rural areas. However, this stagnation conceals a statistically significant increase in CAD mortality rates since 2009 in women aged 55 to 64 years (estimated annual percentage change: +1.4%; 95% CI, +0.3% to +2.5%) and since 1999 in women aged 45 to 54 years (estimated annual percentage change: +0.6%; 95% CI, +0.2% to 1.0%). Since 1999, mortality has been stagnating in the youngest group (aged 35-44 years; estimated annual percentage change: +0.2%; 95% CI, -0.4% to +0.8%). Stratification by race indicated an increase in mortality rates among white rural women. Premature CAD mortality remains consistently higher in the rural versus urban United States, regardless of sex, race, and age group. Conclusions Premature CAD mortality rates have declined over time. However, stratification by sex and urbanization reveals disparities that would otherwise remain concealed: CAD mortality rates have increased among women from rural areas since at least 2009.